PENGARUH GREEN VALUE DAN EMOTIONAL VALUE TERHADAP REPURCHASE INTENTION YANG DIMEDIASI OLEH PERCEIVED QUALITY PADA KONSUMEN PRODUK KECANTIKKAN INNISFREE DI KOTA MEDAN - Nathania Safira Aqilah; Farid Farid (Departemen Manajemen, 2021)
The purpose of this research is to analyze the influence green value and emotional value towards repurchase intention mediated by perceived quality on consumer beauty product Innisfree in Medan. The sample in this research consisted of 200 consumer of product Innisfree in Medan. The sampling technique uses a probability sample and the type of sampling is purposive sampling. Tools uses in collecting data is the form of questionnaire. Researchers used a structural equation modeling (SEM) as method in analyzing the influence of the variabels in this research. Based on the result analyze, it was found that there was an influence of green value and emotional value on perceived quality, while on green value and emotional value there was no influence of repurchase intention. And perceived quality is able to mediate green value and emotional value on repurchase intention.